Responsive Mn‐Ferrite Nanoparticles for Multicolor Magnetic Particle Imaging, Sensing, and Reactive Oxygen Species Degradation - Fabian H. L. Starsich; Julia Feye; Robert Niβler; Gabriela Da Silva André; Elena Totter; Konrad Scheffler; Florian Thieben; Erik Mayr; Jochen Franke; Tobias Knopp; Inge K. Herrmann (Advanced Sensor Research)
Abstract New possibilities offered by Magnetic Particle Spectroscopy (MPS) and Imaging (MPI) are increasingly being recognized and may accelerate the introduction of MPI into clinical settings. As MPI is a tracer‐based imaging method, the design and development of responsive tracers for functional imaging are particularly appealing. Here, Mn‐ferrite (MnxFe3‐xO4) nanoparticles with finely tuned magnetic properties and enzyme‐like capabilities are reported as potential multifunctional theranostic agents. By adjusting the Mn content in the iron oxide matrix, the magnetic particle imaging signal of different tracers can be tweaked, allowing for the simultaneous quantitative detection of two different tracers in a multi‐color approach. The Mn2FeO4 tracers exhibit potent enzyme‐like catalytic properties, enabling degradation of reactive oxygen species, including H2O2 and OH−. Due to the readily interchangeable oxidation states of Mn and Fe atoms in the crystal structure, a strong dependence of the magnetic properties is observed on H2O2 exposure, which can be exploited for sensing. This enables, for the first time, the sensing of reactive oxygen species based on magnetic particle spectroscopy and imaging, with sensitivity down to 25 µm H2O2 and complete sensor recovery over time. In summary, Mn‐ferrite nanoparticles hold promising potential for imaging, sensing, and degradation of disease‐relevant reactive oxygen species.